EKSOTISME PAKISTAN DAN INDIA DALAM “THE HOLY WOMAN” DAN “TYPHOON” KARYA QAISRA SHAHARAZ - Zahra, Siti; A’ida, Wanda Nur; Azam, Zidan Khairul; Nurholis, Nurholis (Cahaya Ilmu Bangsa Institute, 2024)
This study investigates the use of exoticism in Qaisra Shahraz's novels The Holy Woman and Typhoon. Exoticism in literature extends beyond depicting foreign cultures, often functioning as a lens to critique social realities through stereotypes and cultural symbolism. This research employs a qualitative descriptive method, focusing on how Shahraz uses exotic elements to portray the complexity of gender, identity, and power dynamics in Pakistan. The study compares Shahraz’s works with Taj by Timeri N. Murari and Beneath a Marble Sky by John Shors, which showcase exoticism within Indian cultural contexts. The findings reveal that in The Holy Woman, exoticism highlights patriarchal traditions and social inequalities, particularly through rituals like making women